Petrophysical Characterization of Reservoirs in the Pil and Bue area,Norwegian Sea - Berhe, Endrias Hailu (NTNU, 2017)
This thesis presents Petrophysical characterization of Pil and Bue oil and gas bearing shaly sand reservoirs in offshore Norwegian Sea, Norway. In the petroleum industry, interpreting and analyzing logs from shaly sand formations are difficult tasks. The main challenges of water saturation estimation and general petrophysical analysis of rock properties in shaly sand reservoirs are mainly caused by the conductive behavior associated with the clay minerals. The presences of these minerals create vertical and horizontal heterogeneity in the geological formation and finally to the physical properties. Moreover, this thesis project assesses the clean sand and shaly sand methods of water saturation, correcting and correlating of the core porosity and core permeability with the log data results of porosity and permeability. In the analysis of the parameters, Techlog software was used to perform the computations of the petrophysical properties. Three wells (6406/12-3S, 6406/12-3B and 6406/12-3A) were evaluated, and from these wells oil and gas-bearing reservoir was encountered in well 6406/12-3S. However, in well 6406/12-3B and well 6406/12-3A only oil-bearing reservoirs were encountered. Based on general and detailed evaluation of the petrophysical parameters of these wells different values were recorded. The shale volume determined in the reservoirs intervals of well 6406/12-3S, 6406/12-3B and 6406/12-3A lies in a range of 9-20 %, 15-32 %, and 5-33 % respectively. The average grain density used in the log analysis of the three wells was 2.65 g/cc. The reservoir rock properties of the three wells as calculated from the log analysis and values taken from core analysis report shows good to very good reservoir quality. The porosity in well 6406/12-3S ranges between 9-16 % from log analysis and 14-15% from core analysis, in well 6460/12-3B lies in a range of 9.3-14.5 % from log analysis and 12.9 % from core analysis, and in well 6406/12-3A lies in a range of 9-17 % from log analysis. The water saturation in the reservoir ...